The Dynamic Holistic Development of Human Potentials and Wellbeing: Implication on Educational Policies - Rosadah Abd Majid; Manisah Mohd Ali; Norshidah Mohd Salleh; Aliza Alias; Ramesh Kanapathy; Khadijah Said Hashim (Journal of ICSAR, 2018)
Education plays an important role in its mission to develop every individual student to become the best person whose potential has been developed to optimal level. This paper discusses a framework of individual’s holistic potential development. Holistic education includes processes and efforts to realize the progress of individual potentials from all dimensions which include; physical, social, intellect, emotion, aesthetic, creativity, and spirituality or as referred by Malaysian Educational Philosophy as physical, emotion, spiritual, and intellect. Holistic developmental process is regarded as the aim and effort to develop individuals to be mindful and skillful to benefit self and the society at large. Development of social responsibility is the outermost circle of the conceptual framework. It signifies the individual’s awareness of his purpose in life, for continuous wellbeing and happiness when he benefits other people from his potential development. Individual potential development starts from the innermost circle describing his self-development, developing wellbeing, to feel peace and calm, and worthiness. Innermost circle refers to the individual state of happiness or wellbeing when his spiritual dimension is fulfilled and developed. The middle or second circle of the framework refers to the developmental process of character and excellence for individual’s optimal potential development through adults caring and teachers’ application of ‘love pedagogy’. Among the catalysts for the developmental process are: conducive environment, emotional strength and self-actualization, chance factor, time investment, effort, and financial resource. Individual development at the micro level during childhood age will become elements for the developmental process during adolescents and adulthood. Implications of the framework of individual’s holistic potential development on educational policies will be discussed in this paper.